Italian Renaissance art understanding its meaning - Joost-Gaugier, Christiane L. (Chichester, West Sussex, UK Wiley-Blackwell, 2013)
"Richly illustrated, and featuring detailed descriptions of works by pivotal figures in the Italian Renaissance, this enlightening volume traces the development of art and architecture throughout the Italian peninsula in the fifteenth and sixteenth centuries. A smart, elegant, and jargon-free analysis of the Italian Renaissance - what it was, what it means, and why we should study it. Provides a sustained discussion of many great works of Renaissance art that will significantly enhance readers' understanding of the period. Focuses on Renaissance art and architecture as it developed throughout the Italian peninsula, from Venice to Sicily. Situates the Italian Renaissance in the wider context of the history of art. Includes detailed interpretation of works by a host of pivotal Renaissance artists, both well and lesser known."--Provided by publisher.
"Richly illustrated, and featuring detailed descriptions of works by pivotal figures in the Italian Renaissance, this enlightening volume traces the development of art and architecture throughout the Italian peninsula in the fifteenth and sixteenth centuries."--Provided by publisher.
Frontispiece: Map Showing Places Mentioned Preface Introduction: The Italian Renaissance - An Idea Rather than a Period Chapter 1: What a Difference a Hundred Years Makes Chapter 2: How it All Started - Florence and Umbria Chapter 3: What Happened Next in Florence Chapter 4: Searching for the Renaissance in Siena and Southward to Sicily Chapter 5: Searching the Renaissance from Northern Italy Back to Umbria Chapter 6: The Triumph of the Intellectual Avant-Garde - The High Renaissance Chapter 7: Some Other Artists of the High Renaissance Chapter 8: The Swan Song of Renaissance Art Chapter 9: The Break and the New Avant-Garde - Early Mannerism Chapter 10: What Was the Italian Renaissance? Conclusions in the Bigger Picture.
Includes bibliographical references (pages 262-266) and index.
Keywords: Art, Renaissance -- Italy; Art, Italian -- 15th century; Art, Italian -- 16th century